RADIOLARIAN AGE AND LITHOSTRATIGRAPHY OF LATE CRETACEOUS PELAGIC SEDIMENTS OVERLYING BASALTIC EXTRUSIVE ROCKS, NORTHERN OMAN MOUNTAINS - Hara, Kousuke; Kurihara, Toshiyuki (Ofioliti, 2017)
A detailed radiolarian biostratigraphy of pelagic sediments overlying basaltic extrusive lavas of the Oman Ophiolite is reported for the type locality of the Suhaylah Formation near the Wadi Jizzi River, northern Oman Mountains. The extrusive lavas in the studied section are classified as V1 lava produced by mid-ocean-ridge magmatism. The sedimentary succession in the type section (ca. 18 m thick) is subdivided into three units (in stratigraphic order): metalliferous sediments (Unit 1), red mudstone intercalated with radiolarian chert (Unit 2), and micritic limestone (Unit 3). The recovery of well-preserved radiolarians from all units led to the recognition of three distinctive assemblages: Assemblage A, obtained from metalliferous sediments and chert intercalations within red mudstone, could be correlated with the middle-late Cenomanian fauna; Assemblage B, recovered from red mudstone and chert, is assigned to the early Turonian, based on correlation with radiolarian occurrences across the Cenomanian-Turonian boundary; Assemblage C, recognized in micritic limestone, is broadly identified as Turonian-Coniacian. The age of the Suhaylah Formation has previously been interpreted as early Cenomanian to Coniacian-Santonian; however, the revised age could be from late Cenomanian to Turonian-Coniacian. The estimated possible maximum age of metalliferous sediments (96.5-93.9 Ma) is in good agreement with high-precision U-Pb zircon dates of ophiolite crust attributed to ridge magmatism. The depositional age of the pelagic sediments clearly indicates that the ridge magmatism had ended by ca. 95.5 Ma.